Eighth International Chorea–Acanthocytosis Symposium: Summary of Workshop Discussion and Action Points. (15th February 2017) - Pappas, Samuel S.; Bonifacino, Juan; Danek, Adrian; Dauer, William T.; De, Mithu; De Franceschi, Lucia; DiPaolo, Gilbert; Fuller, Robert; Haucke, Volker; Hermann, Andreas; Kornmann, Benoit; Landwehrmeyer, Bernhard; et al.
Chorea-Acanthocytosis (ChAc) is a rare hereditary neurological disorder characterized by abnormal movements, red blood cell pathology, and progressive neurodegeneration. Little is understood of the pathogenesis of ChAc and related disorders (collectively Neuroacanthocytosis). The Eighth International Chorea-Acanthocytosis Symposium was held in May 2016 in Ann Arbor, MI, USA, and focused on molecular mechanisms driving ChAc pathophysiology. Accompanying the meeting, members of the neuroacanthocytosis research community and other invited scientists met in a workshop to discuss the current understanding and next steps needed to better understand ChAc pathogenesis. These discussions identified several broad and critical needs for advancing ChAc research and patient care, and led to the definition of 18 specific action points related to functional and molecular studies, animal models, and clinical research. These action points, described below, represent tractable research goals to pursue for the next several years.